ANALYSIS OF FINANCIAL RATIOS TO ASSESS FINANCIAL PERFORMANCE AT PT. UNILEVER INDONESIA TBK - Tri Damayanti; Nur Halimah (Asosiasi Dosen Muda Indonesia, 2023)
This study aims to analyze the financial performance of PT. Unilever Indonesia Tbk during the 2012-2021 period seen from the Liquidity Ratio, Solvency Ratio, and Profitability Ratio. The data analysis technique used is financial ratios, namely liquidity ratios, solvency ratios, and profitability ratios. The results of the study show that: Liquidity ratios with measuring instruments using current ratios, very current ratios and cash ratios show